Analyses of phenotype and ARGOS and ASY1 expression in a ploidy Chinese cabbage series derived from one haploid - Gu, Ai Xia (Breed Sci, 2016)
The aim of this research was to improve our understanding of how ploidy level influences phenotype and gene expression in Chinese cabbage (Brassica rapa L. ssp. pekinensis). Haploid plants (2n = 10) was induced by 0.2% colchicine to produce diploid (2n = 20) and tetraploid plants (2n = 40). The aneuploid (2n = 24) was also obtained by hybridization between diploid plants as the female and tetraploid plants. The ploidy levels of all plants were identified through chromosome counts and flow cytometry. Leaves and petals became larger as the ploidy level increased from haploid to diploid, and from aneuploid to tetraploid. Similarly, expression of ARGOS was regulated by genome size, increasing in parallel with the level of ploidy. Among the four ploidy types, expression was stronger in the floral buds than in the leaves. Expression by ASY1 also differed according to ploidy level, being highest in diploid plants, followed in order by tetraploids. Expression was similar between haploids and aneuploids at two stages—prior to and after meiosis—but was higher in the haploids during meiosis. When buds were compared within the same ploidy type at different stages, ASY1 expression was obviously higher during meiosis than either before or after. Our study demonstrated the generation and phenotype of a ploidy Chinese cabbage series derived from one haploid. Expression of genes ARGOS and ASY1 were modulated by genome size in this ploidy series, and the regulated patterns of the two genes was different.